Reincarnation in Clement of Alexandria: salvific cycles and steps of progress - Yli-Karjanmaa, Sami (Vigiliae Christianae, 2025)
"International scholarly consensus holds that despite his obvious Platonic sympathies, Clement of Alexandria (ca. 150-215 CE) rejected the doctrine of reincarnation. This study finds that this consensus does not do justice to what Clement actually writes. In his most explicit statement, Clement singles out reincarnation as the example he wants to give of the finest doctrines of the best philosophers. Though most of Clement's other writing is more subtle than that, endorsement is still the most plausible explanation of what he says. The tenet - clearly esoteric for Clement - is in harmony with his anthropology, ethics, and his synergistic soteriology that includes the crucial role of Jesus"-- Provided by publisher